Clinical outcomes of percutaneous coronary intervention for chronic total occlusion by treated segment length. Issue 2 (19th November 2021) - Shoaib, Ahmad; Spratt, James C.; Curzen, Nick; Wilson, Simon; Rashid, Muhammad; Ahmad, Fatima; Ludman, Peter; Kinnaird, Tim; Mamas, Mamas A.; ,
Abstract: Background: Long lesions are known to have worse outcomes following percutaneous coronary intervention (PCI), but there are limited data assessing the association between lesion length and clinical outcomes in PCI procedures undertaken in chronic total occlusions (CTO). Methods and results: We formed a longitudinal cohort (2006–2018, n = 27, 205) of stable angina patients who underwent PCI to CTO in the British Cardiovascular Intervention Society (BCIS) database. Clinical, demographical, procedural, and outcome data were analyzed in three groups by treated segment length, < 30 mm ( n = 11, 782), 30–59 mm ( n = 10, 415), ≥ 60 mm ( n = 5008). Prevalence of previous myocardial infarction and PCI were higher in patients in 30–59 mm group or ≥ 60 mm group compared with < 30 mm group. Following multivariable analysis, no significant difference was observed in in‐patient death (OR = 30–59 mm group = 1.10, CI:0.55–2.19, p = 0.78) (OR ≥ 60 mm group = 0.82, CI: 0.33–2.05, p = 0.67), and 1‐year death (OR = 30–59 mm group = 1.06, CI: 0.81–1.37, p = 0.69) (OR ≥ 60 mm group =1.01, CI: 0.70–1.43, p = 0.99) (< 30 mm group = reference) but in‐patient MACE was higher in > = 60 mm group (OR: 1.52, CI: 1.15–2.01, p = 0.06) but similar in 30–59 mm group (OR: 1.16, CI: 0.91–1.48, p = 0.22) compared with < 30 mm group. The adjusted rates of procedural complications were higher in ≥ 60 mm group (OR: 1.61, CI: 1.40–1.85, p < 0.001) but were similar in 30–59 mm group (OR: 1.06, CI: 0.94–1.20, p < 0.31) compared with < 30 mm group. For every 10 mm increase, there was an increased adjusted risk of in‐patient procedural complications and coronary perforation but not in‐patient MACE or death. Conclusion: Patients with very long CTO lesions have higher risk of procedural complications and in‐patient MACE but similar risk of short or long‐term mortality compared with short CTO lesions.